Students’ Mathematical Literacy in GeoGebra-Assisted Mathematics Learning: A Systematic Literature Review - Fauzi, Nanda Akmala; Waluya, St Budi; Zaenuri, Zaenuri; Walid, Walid (Media Pendidikan Matematika, 2026)
Educational developments in the 21st century emphasize the importance of mathematics learning that can improve students’ mathematical literacy. This study aims to systematically examine research trends related to students’ mathematical literacy in GeoGebra-assisted mathematics learning. The method used is a Systematic Literature Review (SLR) of 12 articles published in the 2020–2025 period and obtained through the Google Scholar and Crossref database with the help of the Publish or Perish application using the keywords mathematical literacy and GeoGebra. The results of the study show that the use of GeoGebra in the last five years has been increasingly researched, with a focus on strengthening mathematical literacy through various innovative learning models, including Problem-Based Learning, Project-Based Learning, Discovery Learning, Realistic Mathematics Education, Think-Talk-Write, and the Missouri Mathematics Project. In conclusion, GeoGebra-assisted mathematics learning can improve students’ mathematical literacy sustainably and in accordance with the context of 21st-century learning.